Introducing research methodology a beginner's guide to doing a research project - Flick, Uwe 1956- (Sage Publications, 2011)
'Introducing Research Methodology' gives readers the fundamental data collection and analysis skills that they need for their first project, as well as a good understanding of the research process as a whole.